Brucellosis-associated hemophagocytic lymphohistiocytosis: a case report and literature review - Jiang, Shuwen; Xia, Binfeng; Wu, Hongyu; Zhang, Peng; Li, Xiaohua; Zhang, Kaiyu (Frontiers in Medicine, 2025)
IntroductionHemophagocytic lymphohistiocytosis (HLH), a rare and deadly disease, is typically classified as either primary (familial) or secondary (acquired), depending on the etiology and underlying cause. Secondary HLH often develops in the presence of infectious, malignant, rheumatologic, or metabolic conditions, with infections, especially Epstein–Barr virus (EBV) infection, being among the leading causes. Brucella infection-induced HLH is relatively rare, with only eight cases reported in the past decade, all of which had a favorable prognosis following timely diagnosis and treatment.Case descriptionA 53-year-old man with brucellosis who developed secondary HLH and multiple organ dysfunction presented to our hospital with a 2-month history of fever and abnormal liver enzymes. Initial blood culture following admission confirmed Brucella spp. in the aerobic bottle after ⁓87.85 h of incubation. However, after the initial discharge, the patient did not adhere to the prescribed antibiotic therapy and subsequently developed symptoms of fever and abdominal discomfort, and was readmitted to our hospital. Laboratory examination also revealed pancytopenia. An additional blood culture further revealed the growth of Brucella spp. in the aerobic bottle after ⁓113.67 h of incubation. Other findings included decreased fibrinogen, increased ferritin, increased soluble IL-2 receptor α chain (sCD25), decreased Natural Killer (NK) cell activity, presence of hemophagocytic cells in the bone marrow smear, splenomegaly, and abnormal liver and kidney functions. The HScore score was 230 points. A thorough assessment was made, which led to the exclusion of other possible diseases, culminating in the identification of Brucella infection as the most probable cause of HLH. Consequently, the patient was given anti-infection (doxycycline, levofloxacin, etimicin, and rifampin), glucocorticoids (GCs), human immunoglobulin (HIG), and other symptomatic supportive treatments, which ultimately improved his condition.ConclusionDespite the generally poor prognosis of HLH patients, those with Brucella-induced HLH may have a favorable outcome with prompt intervention. Conversely, a delayed treatment could increase the risk of HLH onset and progression, leading to death in severe cases.